Sharia Fintech As An Instrument Of National Economic Recovery Amid The Covid-19 Pandemic - Nurul Istifadhoh; Inarotul A’yun; Hafidhotul Mufidhoh (Universitas Trunojoyo Madura, 2021)
The focus of this research is to uncover the existence of sharia fintech which is considered able to accelerate the process of accelerating economic recovery due to pandemics that have an impact on the slowdown of the national scale economy.This research was conducted using an in-depth literature study with qualitative descriptive analysis techniques approach. The data collection method used is the library method. The literature used as a reference is scientific articles, mass media articles, textbooks, and other online literature searches that correspond to this research.The results of the study show fintech contributes positively to the national economic recovery and the increase in state revenues during the pandemic. This can be improved by supporting strengthening government regulations for inclusive and sustainable fintech growth so that fintech has the potential to be a triggering factor for the digital financial services industry in Indonesia.